Overstepping the upper refractive index limit to form ultra-narrow photonic nanojets - Guoqiang Gu (Nature Portfolio, 2017)
Abstract In general, photonic nanojets (PNJs) occur only when the refractive index (Ri) difference between the microparticle and background media is less than 2. The minimum full width at half-maximum (FWHM) of the PNJ is ~130 nm (approximately one-third of the illumination wavelength λ = 400 nm) formed within the evanescent field region. This paper proposes and studies a method to overstep the Ri upper bound and generate ultra-narrow PNJs. Finite element method based numerical investigations and ray-optics theoretical analyses have realized ultra-narrow PNJs with FWHM as small as 114.7 nm (0.287 λ) obtained from an edge-cut, length-reduced and parabolic-profiled microparticle with Ri = 2.5 beyond evanescent decay length. Using simple strain or compression operations, sub-diffraction-limited PNJs can be flexibly tuned on the order of several wavelengths. Such ultra-narrow PNJs offer great prospects for optical nonlinearity enhancements of greater enhancing effect, optical nanoscopy of higher spatial resolution, optical microprobes of smaller measurement accuracy, nano/micro-sized sample detections of higher sensing sensitivity, nanoscale objects of more accurate control, advanced manufactures of smaller processing size, optical-disk storage of larger data capacity and all-optical switching of lower energy consumption.